A Model-Based Strategy for Interturn Short-Circuit Fault Diagnosis in PMSM - Mazzoletti, Manuel Armando (2017)
A model-based method for interturn short-circuit fault detection and isolation in permanent magnet synchronous machines (PMSMs) is proposed in this paper. The fault detection is realized based on a residual current vector (RCV) generated by the difference between the measured stator currents and the stator currents estimated by a state observer. In order to avoid false alarms due to possible undesired perturbations, the sequence decomposition of the RCV is performed by employing different reference-frames. Thus, the proposed RCV allows the correct detection of interturn short-circuit faults and quantification of the fault severity in any faulty stator-phase winding. Moreover, since the back-EMF generated by the magnets is proportional to the rotor shaft speed, the electrical angular speed is estimated through the stator voltages measurement, without using a speed sensor. Simulation results from the three-phase PMSM dynamic model that allows considering the interturn short-circuit fault in any stator phase-windings are presented. The proposed method is validated using a three-phase PMSM prototype with modified stator windings. The robustness and the reliability of the proposal was tested for several interturn fault conditions under transient conditions including different disturbances.